Short-Term Effects of Low-Head Barrier Removals on Fish Communities and Habitats - Bubb, Damian H.; Birnie-Gauvin, Kim; Tummers, Jeroen S.; Aarestrup, Kim; Jepsen, Niels; Lucas, Martyn C. (Frontiers in Ecology and Evolution, 2021)
Barrier removal is increasingly being seen as the optimal solution to restore lotic habitat and fish communities, however evidence of its efficacy is often limited to single sites or catchments. This study used a before-after methodology to examine the short-term (average, 541 days) effects of low-head (0.1-2.9 m) barrier removal at 22 sites distributed across Denmark and northern England on fish density, community and river habitat responses. Following barrier removal, changes in the aquatic habitat were observed, such that the area immediately upstream of the former barrier location became shallower, with larger substrate and faster flow conditions. The reinstatement of this habitat wasis especially valuable in Danish streams, where these habitat features are rare, due to the naturally low gradients. Across all 22 sites fish species richness and diversity was similar before and after removal of barriers, likely because of the short study timescale (1-2 years). Across all sites combined, there was an increase in total fish density following barrier removal. A large increase in salmonid (Salmo trutta and Salmo salar) densities following barrier removal occurred at 7 out of 12 Danish sites. No similar response in salmonid density was observed at any of the UK sites which were mostly characterized by high channel gradients and short ponded zones. Two UK barrier removal sites showed marked increases in density of non-salmonid fish species. This study suggests that the removal of low-head barriers can be an effective method of restoring lotic habitats, and can lead to positive changes on the fish density. The short-term effect of small barrier removal on the fish community is more variable and its effectiveness is likely to be determined by wider riverine processes.